Professional practice Loma de San Pedro School - Avendaño González, Yaritza L. (UDELAS, 2010)
Professional practice mau represent a valuable and important experience for students from the educational point of view as to face the reality that involves the exercise of it, significantly enriches the future professional; you can complement the knowledge and develop practical skills, values and attitudes acquiried during their training.